Press, War and Propaganda in Malaya: Issues in Malai Shinpo and Syonan Shimbun - Fathil, Fauziah; Fathil, Fathiah (UPNM Press, 2016)
The advent of Japanese to Malaya in 1941 saw the suspension of existing pre-war press or newspapers and in their place, new publications appeared, of which Malai Shinpo and Syonan Shimbun stood out. Not only did they last longer and more regular but can also be found in abundance compared to others. More importantly, having adopted a pro-Japanese stance, the two newspapers served as propaganda tools for the Japanese war campaign in Malaya. The research attempts to cover the various issues discussed in the newspapers especially those related to Japanese propaganda. Any changing tones in the issues or matters covered in the newspapers were examined by looking at the possible reasons that might have contributed to the changes that took place and for this purpose, the changing war-time situations or scenarios were assessed. Moreover, the paper highlights efforts on the part of the Japanese to have the locals assimilated their spirit or culture (seishin) i.e. Japanization of the locals, which one can argue is also related to Japanese war propaganda. The method employed in conducting the research is a qualitative and library research where archival and non-archival documents were sought at the Malaysian National Archives and national libraries. The findings of this paper not only enrich the information on the history of the Japanese occupation of Malaya but also provide more information on the development of press or newspapers in the first half twentieth century Malaya, a topic which has not been widely studied until now.